Comparative analysis of higher education on the example of certain countries of the European and Asia-Pacific regions - S. E. Titor; S. V. Cherkasova (Вестник университета, 2024)
This study analyses and compares higher education in Germany, France, and Singapore. The authors highlight the similarities and differences between higher education systems in some countries of the European and Asia-Pacific regions. Its structure is described, with consideration to characteristics of each state, the place of these countries in the leading world rankings on the level of education is given (Education Index 2022 of the United Nations Development Programme and Human Development Report 2021–2022). A comparative analysis of the study duration, principles of building a higher education system was conducted. Also, the authors studied participation of employers (organisations and enterprises) and state in the process, along with issues of employment of graduates as a criterion for this method. The role of the relative independence of higher educational institutions in resolving admission issues was identified. The authors examined the stages of mastering programmes, the requirements for applicants when entering educational organisations, the types of degrees, and the procedure for awarding them. The system of dual (practice-oriented) training was explored as a basis for employment of graduates in France and Germany, the principles and goals of its functioning in the analysed states of the European region were clarified.